FEATURES OF CHRONIC KIDNEY DISEASE IN PATIENTS WITH ARTERIAL HYPERTENSION (International Conference on Modern Science and Scientific Studies, 2025)
Arterial hypertension (AH) is currently both a cause and a consequence of chronic kidney disease. Numerous clinical studies have shown the importance of blood pressure control. However, it remains unclear how important blood pressure control is in patients with chronic kidney disease (CKD). CKD is characterized by accelerated vascular aging, in which an age-related increase in arterial stiffness is aggravated by a number of uremia-related processes. Increased arterial stiffness is associated with structural and functional disorders, as well as an increase in cardiovascular mortality in patients with CKD. CKD is characterized by accelerated vascular aging, in which an age-related increase in arterial stiffness is aggravated by a number of uremia-related processes. Increased arterial stiffness is associated with structural and functional disorders, as well as an increase in cardiovascular mortality in patients with CKD.